(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
The Syrian society is facing significant challenges in the field of disability with all its classifications, in particular the Physically disability that we discussed in this research by revealing the extent to which Syrian laws on disability are applied in different areas of life. In addition to identifying the most prominent difficulties that facing this segment in their daily lives, as well as their most prominent needs for social integration. The descriptive analytical method was used to study and describe the reality of the physically disabled in terms of the extent of benefiting from the Syrian laws related to the range of services that should be provided in several areas, in order to enable them to practice their daily lives with minimal effort The interview was adopted as a means of gathering information, The interview was conducted with a sample of (10) persons with Physically disabilities in the Syrian Society for the Physically Disabled in Lattakia city, during which the study questions were answered.